Vocabulary Breadth and Depth in Early School-Aged Children with Developmental Language Disorder - Evidence from Serbian Speaking Children - Bojana Drljan; Nevena R. Ječmenica; Ivana P. Arsenić (National Research University Higher School of Economics, 2023)
Objectives. Taking into account the positive association observed between lexical abilities and academic performance in children, this research aims to compare the expressive vocabulary skills and the organization of the lexical-semantic network in early school-aged children diagnosed with developmental language disorder (DLD) and their typically developing (TD) peers. Method. The sample included 57 participants (aged 7 and 8 years), 27 children diagnosed with DLD and 30 TD children. The Boston Naming Test and Word Association Task were employed to assess lexical abilities. Results. The findings revealed that children with DLD produced significantly fewer correct answers and a higher number of errors during the naming task when compared to their typically developing peers. Moreover, children with DLD provided significantly fewer developmentally mature types of associations and significantly more developmentally immature ones. Conclusion. The study results indicate that children with DLD continue to display significant lexical deficits during school-age, encompassing both vocabulary breadth and depth. These findings highlight the importance of implementing additional intervention approaches that focus on semantic aspects to prevent further language deterioration and mitigate the potential negative impact of lexical impairments on the academic achievements of these children.